Gender and socio-demographic distribution of body mass index: The nutrition transition in an adult Angolan community - João M. Pedro; Miguel Brito; Henrique Barros (AOSIS, 2018)
This cross-sectional survey with 2357 subjects aged 15 to 64 years from a ruralurban community in Bengo Province, Angola, aimed to evaluate the gender differences in the prevalence of body mass index categories and how socio-demographic characteristics influence it. Women presented a significantly higher prevalence of obesity (10.5% versus 2.8%) but the underweight frequency was similar to men (10.2% versus 12.4%). Overweight and obesity increased with age, with underweight being more prevalent in the age group 15 to 24 years. Obesity was more prevalent among individuals living with a companion (in a marital relation), decreased with education (in women), but was higher in rural areas, and for those with a higher family monthly income, in both genders. The prevalence of obesity and underweight were similar in women, reflecting a nutrition transition state. Like in other African communities, women present a higher prevalence of overweight and obesity them men, but the values of underweight are similar between genders. This stresses the need of designed health interventions for women, to face the double burden and accumulation of risk factors in women.